NEW CAMBRIAN LOBOPODS AND CHAETOGNATHS OF THE SIBERIAN PLATFORM - Demidenko Yu.E. (My University, 2006)
The association of isolated remains of lobopods with a netlike structure, including plates of Microdictyon rozanovi sp. nov. and sclerites with spinelike process of Onychomicrodictyon spiniferum gen. et sp. nov., as well as saberlike sclerites of Protohertzina yudomica sp. nov. interpreted as grasping spines of chaetognaths, is described from the middle part of the Inikan Formation of the Toyonian Stage of the Lower Cambrian (Lermontovia dzevanovskii Zone). The diagnoses and species composition of the genera Microdictyon and Protohertzina are refined. © Pleiades Publishing, Inc. 2006.
Keywords: CHAETOGNATHA; EARLY CAMBRIAN; LOBOPODS; PROTOCONODONTS; RUSSIA; SIBERIAN PLATFORM; TOYONIAN STAGE; YUDOMA RIVER; Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская